PERSPEKTIF “AL-ILM” MENURUT AL-QUR’AN DAN ULAMA SALAFI DI DALAM TATANAN PENDIDIKAN ISLAM - ummu kulsum (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2020)
Abstract, Knowledge is the light of knowledge that is passed by reading or known as Iqra 'in the Qur'anic language, besides that many conventional scholars give meaning to the concept of